Seismic Sedimentology for the Characterization of Quaternary Evaporite Facies in Biogas-Bearing Taidong Area, Sanhu Depression, Qaidam Basin, NW China - Guoyong Liu; Zhaohui Xu; Jiangtao Li; Yong Song; Hongliu Zeng; Xiaomin Zhu; Jixian Tian; Chunming Lin; Lei Jiang (Applied Sciences)
S-wave seismic data are unaffected by natural gas trapped in strata, making them a valuable tool to study evaporite facies comparing to P-wave data. S-wave seismic data were utilized to construct an isochronous framework and analyze evaporite facies by seismic sedimentology methods in the Quaternary biogenic gas-bearing Taidong area, Sanhu Depression, Qaidam Basin, NW China, with calibration from wireline logs, geochemical evidences, and modern analogs. Techniques of phase rotation, frequency decomposition, R (Red), G (Green), B (Blue) fusion, and stratal slices were integrated to reconstruct seismic geomorphological features. Linear and sub-circular morphologies, resembling those observed in modern saline pans such as Lake Chad, were identified. Observations from Upper Pleistocene outcrops of anhydrite and halite at Yanshan (east of the Taidong area), along with lithological and paleo-environmental records from boreholes SG-5, SG-1, and SG-1b (northwest of the Taidong area), support the seismic findings. The slices generated from the S-wave seismic data indicate a progressive increase in the occurrence of evaporite features from the K2 standard zone upwards. The vertical occurrence of evaporite facies in the Taidong area increases, which coincides with the contemporary regional and global arid paleo-environmental changes. The interpretation of Quaternary stratal slices reveals a transition from a freshwater lake to brackish, saline, and finally, a dry saline pan, overlaid by silt. This analysis provides valuable insights into locating evaporites as cap rocks for biogenic gas accumulation and also into mining the evaporite mineral resources in shallow layers of the Taidong area.